PlastiCRISPR: Genome Editing-Based Plastic Waste Management with Implications in Polyethylene Terephthalate (PET) Degradation - Puja Palit; Maya Minkara; Maisha Abida; Safa Marwa; Chandrima Sen; Ayan Roy; Md Ridoan Pasha; Paulraj Selvakumar Mosae; Ayan Saha; Jannatul Ferdoush (Biomolecules)
Plastic pollution has become a significant environmental issue worldwide, with global plastic production expected to reach 1800 million tons by 2050. One of the most commonly used plastics in the world is polyethylene terephthalate (PET), a synthetic polymer that is extremely durable but difficult to degrade. Thus, PET is dangerous to human health. To address this crisis, innovative approaches are being developed, including genome editing technologies. One of the recently advanced genome editing technologies is PlastiCRISPR, a novel concept that applies CRISPR-based genome editing to transform plastic waste management. PlastiCRISPR utilizes microorganisms to degrade plastic, generating valuable bioproducts like biofuels and biochemicals. Thus, this technology offers a sustainable solution because of its simple design, adequacy, and low cost, which can be integrated into existing waste management systems. Importantly, this review focuses on the PlastiCRISPR-based management of PET because it could drastically lower plastic waste, sustain natural resources by decreasing the requirement for plastic production, minimize energy intake, etc. Overall, this review provides an overview of the principles, applications, challenges, and future prospects of PlastiCRISPR in combating plastic pollution and shaping a more sustainable future.